2013
DOI: 10.1021/jp408333h
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Absorption and Ultrafast Luminescence Dynamics of Bi-Icosahedral Au25 Clusters

Abstract: Temperature-dependent absorption and ultrafast luminescence dynamics of [Au25(PPh3)10(SC6)5Cl2 ]2+ (Au25-rod) was studied and compared with [Au25(SC6)18]− (Au25-sphere) and Au38(SC2Ph)24 (Au38-rod) to understand the influence of the crystal structure on the optical properties of monolayer protected gold clusters. The temperature-dependent absorption of Au25-rod shows a shift in the absorption maximum to high energies and a small increase in the oscillator strength with decrease in temperature. The energy shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 66 publications
(103 reference statements)
3
73
0
Order By: Relevance
“…With temperature decreasing from 330 K down to 77 K, three features were observed: (i) both ESA and GSB peaks became sharper and additional peaks emerged, (ii) both the maxima of ESA and GSB evolve to higher energies, and (iii) the intensities of both ESA and GSB increased significantly. The steady-state absorption spectra of Au 25 (SR) 18 , Au 38 (SR) 24 , and rod-shaped Au 25 were reported to exhibit similar behaviors as the temperature decreased (47,48), which was explained by electron-phonon (e-p) coupling and lattice expansion interactions. Here, the blue shift and enhancement of ESA at low temperatures suggest that the ESA is also strongly affected by the e-p coupling effect.…”
Section: Resultsmentioning
confidence: 97%
“…With temperature decreasing from 330 K down to 77 K, three features were observed: (i) both ESA and GSB peaks became sharper and additional peaks emerged, (ii) both the maxima of ESA and GSB evolve to higher energies, and (iii) the intensities of both ESA and GSB increased significantly. The steady-state absorption spectra of Au 25 (SR) 18 , Au 38 (SR) 24 , and rod-shaped Au 25 were reported to exhibit similar behaviors as the temperature decreased (47,48), which was explained by electron-phonon (e-p) coupling and lattice expansion interactions. Here, the blue shift and enhancement of ESA at low temperatures suggest that the ESA is also strongly affected by the e-p coupling effect.…”
Section: Resultsmentioning
confidence: 97%
“…In a previous study, we have shown that the luminescence from quantum-sized gold clusters consists of two components: a weak, low quantum yield visible luminescence followed by near infrared luminescence. [28][29][30] The visible luminescence relaxes in ultrafast time scales and was assigned to core-gold luminescence. To monitor the visible luminescence dynamics of Au 22 clusters, femtosecond measurements were carried out after excitation at 400 nm and monitoring at 520 to 550 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Other quantum-sized gold clusters have also shown similar ultrafast luminescence at this wavelength region, which was assigned to the relaxation of core-gold to shellgold. [28][29][30] Femtosecond luminescence anisotropy measurements have shown zero anisotropy for the visible luminescence indicating that the excitation and luminescence decay are dominantly localized on core-gold states.…”
Section: Resultsmentioning
confidence: 99%
“…The number of Ag atoms in Au NCs affects the S 1 state significantly. Moleculelike efficient internal conversion (IC) (~ 1 ps) was observed before in Au NCs accompanied by core-shell charge transfer [65,66]. Sfeir et al attributed the faster decaying component to rapid IC [67].…”
Section: Resultsmentioning
confidence: 96%